Volleyball Upper Passing Ability of Class X Students of SMK Negeri 1 Martapura - Pangestu, Ragil Aji; Kristina, Putri Cicilia; Hermansah, Bambang (Yayasan Sembilan Pemuda Indonesia, 2023)
The success of a volleyball game is supported by the ability of its players to master various basic volleyball techniques. Top passing is one of the basic techniques in volleyball that students must have. The problem in this study is that the level of volleyball upper passing ability at SMK Negeri 1 Martapura is unknown. This study aims to determine the level of volleyball upper passing ability in students of SMK Negeri 1 Martapura. The variable in this study is a single variable, namely the ability to pass over volleyball. The population in this study were X TKJ 1 class students totaling 36 students, while the sample was taken using total sampling technique so that all populations were sampled in this study. The method in this research is descriptive quantitative with a survey approach. Data collection techniques using the upper passing test instrument. Data analysis using the Percentage Formula. The results showed that the level of upper passing ability in class X TKJ 1 students showed that students who had a good category were 17 students (47%), who had a sufficient category of 13 students (36%), who had a category of less than 6 students (10%). The results show that SMK Negeri 1 Martapura students have a fairly good upper passing ability based on the results that get a good category as much as 47% of the total sampling.